Norms for size and closure time of anterior fontanelle: a study on babies in Nagpur region - Amit Tirpude; M P Fulpatil; Swapan Kole (Wolters Kluwer Medknow Publications, 2016)
Background and aims : Anterior fontanelle development in children is affected by several factors ranging from physical to geographical. While the impact of factors such as gestational age (GA) and gender are clearly established, the influences of region and ethnicity vary in the published literature. The objectives of the study were: 1. To measure the anterior fontanelle size (AFS) and closure time of babies aging from newborn to two years of age in respect to its gender and term status in Nagpur babies. 2. To evaluate the relationship of our findings with growth parameters. Methods : Measurements were done on 808 babies according to Popich and Smith method. Measurements on newborn were done after 48 hours of birth. Z-test of significance and Pearson's correlation coefficient are used for analysis. Results: Mean AFS ranged from4.95±2.15 to 0.94±0.05 cms in preterm babies and 4.24±2.21 to 1.32±0.21 cms in full term babies. Mean AFS ranging from4.48±2.26to 1.31±0.22and4.02±2.20to 1.24±0.13 cms were observed in male and female babies respectively. Study revealed no significant difference in AFS between full term and preterm & male and female babies. Around 20% fontanels are closed around sixth month. Less than 1% fontanels were open around 22-24 months. No significant difference in closure time was found. AF size had significant correlation with growth parameters of full term babies (weight r = - 0.37, p = 0.00) (head circumference r = - 0.30, p = 0.00) (crown heel length r = - 0.39, p = 0.00). AF closure time showed a significant relationship with growth parameters (weight r = 0.77, p = 0.00) (head circumference r = 0.72, p = 0.00) (crown heel length r = 0.85, p = 0.00). Conclusion: AF sizes obtained in this study are recommended for use as local values for reference in assessing term and preterm babies born in Nagpur.